Genotype x larval density interaction in the rearing bed expressed by larval and pupal weight in silkworm, Bombyx mori L. (University Journal of Zoology, Rajshahi University, 2007)
Key words: genotype; larval density; rearing bed; Bombyx mori Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 43-47